Antimicrobial Resistance Patterns in Diabetic Foot Infections: A Microbiological Study in Pakistan - Rehman, Faiza; Imran, Tabbassum; Kanwal, Sughra; Kharal, Mehwish; Farooq, Naveen; Kumar, Gotam; Naeem, Nabiha (Journal of Neonatal Surgery, 2025)
Background: Diabetic foot infections (DFIs) are a major cause of morbidity and amputation worldwide, driven by polymicrobial infections and escalating antimicrobial resistance. Understanding local pathogen distribution and resistance trends is critical for guiding empirical therapy. Objective: To identify bacterial isolates from DFIs, determine their antimicrobial resistance patterns, and assess the association of ulcer severity with multidrug resistance (MDR). Methodology: This cross-sectional study included 150 patients with DFIs. Demographic and clinical data were collected, and specimens were processed for microbiological culture. Antimicrobial susceptibility was assessed using standard methods. Data were analyzed in SPSS v25, with descriptive statistics presented as mean ± SD, median (IQR), and n (%). Chi-square test assessed associations, with p ≤0.05 considered significant. Results: Of 172 isolates recovered, Staphylococcus aureus (31%) was most frequent, followed by E. coli (19%), Klebsiella pneumoniae (15%), and Pseudomonas aeruginosa (12%). MRSA accounted for 10% of S. aureus. Resistance was highest to ceftriaxone (60–81%) and ciprofloxacin (43–70%), whereas imipenem showed the lowest resistance (7–25%). MDR prevalence was 30% in S. aureus, 69% in E. coli, 73% in Klebsiella, and 60% in Pseudomonas. MDR was significantly more common in Wagner grade III–IV ulcers (54%) than in grade I–II (29%) (p=0.012). Conclusion: DFIs in this cohort are characterized by a high burden of Gram-negative pathogens and MDR, especially in advanced ulcers. Early microbiological diagnosis, local antibiogram-guided empirical therapy, and antimicrobial stewardship are essential to improve outcomes and curb resistance.